Introduction to ‘Learning the future otherwise: emerging approaches to critical anticipation in education’ - Amsler, Sarah; Facer, Keri (Elsevier, 2017)
In November 2015, a gathering was convened in Italy to explore how to ‘improve the resilience of societies facing threats from a global proliferation of agents and forces by articulating uncertainties through anticipatory processes’ (Project Anticipation 2015). The First International Conference on Anticipation drew researchers and practitioners from around the world and across disciplines to explore how the future is made into an active part of the historical present, and to debate the cultural, ecological, economic, epistemological, political and social consequences of the ‘anticipatory processes’ which are shaping future-oriented action today (Poli 2017). [...]